A SOCIOCULTURAL APPROACH TO TEACHING A FOREIGN LANGUAGE IN SCHOOL - Hamdamova Nilufar Esanovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article discusses a number of technologies that contribute to students' cultural competence development. The article examines a number of technologies that contribute to the development of students' sosio-cultural competence, including independent educational activity, which determines the ability to practically reorganize activities, resulting in an interlingual and intercultural language personality.